Slip processing of high T c superconductors - Sinha, R.K.; Sinha, R.K. (Springer India, 1991)
Slip-processing technique has been used to fabricate tapes and alumina-supported films of superconducting YBa2Cu3O7-x . Good densification and connectivity are revealed by scanning electron microscopy. Both the tape and film show superconductivity well above the liquid nitrogen temperature with a transition range of 3° and 5°K respectively. © 1991 Indian Academy of Sciences.
Keywords: doctor blade tapes; screen-printed films; slip processing; Superconductivity